Short Term Deflation of Stomach during Laparoscopic Surgery: Nasal versus Oral Route - Quasi-Experimental Study - Iftikhar, Izza; Abdullah, Hassam; Sohail, Amir; Ilyas, Hafiza Ayesha; Saeed, Muhammad; Abdullah, (Pakistan Armed Forces Medical Journal, 2025)
Objectives: To compare the efficacy and complications of orogastric tubes (OGT) versus nasogastric tubes (NGT) for intraoperative gastric decompression in laparoscopic surgeries.Study Design: Quasi-experimental study.Place and Duration of Study: Department of Anesthesiology, Combined Military Hospital, Gujranwala Pakistan, from Jan to Dec 23.Methodology: Patients undergoing laparoscopic cholecystectomy in CMH Gujranwala were included and segregated into two equal groups of 50 each on basis of method used for intra-operative gastric decompression (Orogastric and Nasogastric). The efficacy of method and associated complications of both methods were observed and compared between both groups.Results: The sampled population included 38.0% males and 62.0% females. ASA-I patients constituted 46.0% of the sample size whereas 54.0% belonged to ASA-II. The OG intubation via second ETT was significantly a better method for intraoperative gastric deflation when compared by attempts to pass the tube (p